Coordinated scheduling of generalized energy storage in multi-voltage level AC/DC hybrid distribution network. (January 2023) - Luo, Lizi; He, Pinquan; Gu, Wei; Sheng, Wanxing; Liu, Keyan; Bai, Muke
Abstract: With the diversification of electrical equipment and the large-scale popularization of renewable energy power generation, it has become a broad consensus to use schedulable resources to improve the load level and reduce network losses in power distribution networks. And meanwhile, the coverage of schedulable resources has been significantly extended due to the development of power market and network topology technologies. Based on this background, this paper proposes a coordinated scheduling model of generalized energy storage (GES) in multi-voltage level AC/DC hybrid distribution network, during which the energy storage systems (ESSs), electric vehicles (EVs), as well as transferable loads (TLs) are properly considered, and thereby the interaction in greater extent is realized. Finally, the effectiveness of the proposed model is verified through a 52-node test system, and two comparative scenarios are analyzed. Numerical results indicate that the scheduling scheme obtained from the proposed model can bring about evident reduction in network losses within the whole system. Highlights: Various controllable resources are aggregated as generalized energy storage (GES). An optimization model is proposed for the coordinated scheduling of GES. AC/DC distribution network topology and multi-voltage levels are properly included. The diverse characteristics of GESs related with their access positions are considered.